Application effect of Zhulianhua Gargle in oral care of inpatients with hyperthermia syndrome (竹连花含漱液在实热证住院患者口腔护理中的应用效果) - HAO Tiantian (郝天天); WEI Jinrong (魏金荣); ZHANG Lingyan (张玲燕); QIU Shuang (邱爽); ZHAO Wei (赵伟); GENG Tong (耿桐) (中西医结合护理)
Objective To explore the application effect of Zhulianhua Gargle in oral care of inpatients with hyperthermia syndrome, in order to further promote oral health from the perspective of Traditional Chinese Medicine. Methods From January 2022 to December 2023, 240 hospitalized patients with phlegm-heat stagnation lung syndrome, intestinal damp-heat syndrome, damp-heat obstructing syndrome, and liver-stomach depression heat syndrome were selected and divided into 2 groups, with 120 cases in each group by random number table method. The observation group was treated with Zhulianhua Gargle gargling solution, while the control group was treated with saline gargling solution. The changes of oral pH value, oral bacterial quantitative test, oral function, halitosis value and oral comfort were compared after 2 weeks of intervention. Results Before intervention, there were no significant differences in oral pH value, oral function, halitosis value and oral comfort between the two groups (P＞0. 05). After 2 weeks of intervention, patients in the observation group achieved better outcomes in oral pH value (6. 23±0. 52), oral function score (8. 71±4. 05), halitosis value score (1. 29±0. 61) and oral comfort rate of the observation group(100. 00%), and he difference between the two groups was statistically significant (P＜0. 05). Conclusion Zhulianhua Gargle has a good effect on improving the oral syndrome of hyperthermia, improving oral pH value, oral function, making oral freshness and improving oral comfort. (目的 探讨医院自制竹连花含漱液在实热证住院患者口腔护理中的应用效果, 以期从中医的角度进一步推进口腔健康。方法 选择2022年1月—2023年12月在江苏省扬州市某三甲中医院痰热郁肺证、肠道湿热证、湿热壅滞证、肝胃郁热证等实热证住院患者240例, 采用随机数字表法分为两组, 每组120例。观察组应用医院自制竹连花含漱液, 对照组应用生理盐水含漱液, 口腔护理方法一致。比较干预前和干预2周后患者口腔pH值、口腔细菌定量实验、口腔功能情况、口臭值、口腔舒适度的变化。结果 干预前, 两组口腔pH值、口腔功能情况、口臭值、口腔舒适度结果比较, 差异无统计学差异(P＞0. 05)。干预2周后, 观察组口腔pH值(6. 23±0. 52), 口腔功能得分(8. 71±4. 05)分, 口臭值得分(1. 29±0. 61)分, 口腔舒适度总有效率100. 00%, 且与对照组比较, 差异有统计学差异(P＜0. 05)。结论 竹连花含漱液对改善患者实热型口腔症候疗效方面有良好效果, 能有效改善口腔pH值、口腔功能情况, 使口腔清新, 提高口腔舒适度。)